Endeavours of the Myanmar armed forces government for National Reconsolidation - Yan Nyein Aye ([Rangoon] : U Aung Zaw, 2000)
In post-1988 Burma
Keywords: Burma. -- Tap'ma to'; Burma -- Politics and government -- 1988-